Antigen‐specific TIL therapy for melanoma: A flexible platform for personalized cancer immunotherapy. Issue 6 (3rd May 2016) - Kelderman, Sander; Heemskerk, Bianca; Fanchi, Lorenzo; Philips, Daisy; Toebes, Mireille; Kvistborg, Pia; van Buuren, Marit M.; van Rooij, Nienke; Michels, Samira; Germeroth, Lothar; Haanen, John B. A. G.; Schumacher, N. M.
Abstract : TIL therapy is a novel treatment modality for metastatic melanoma. CD8 + T cells specifically targeting melanoma antigens are considered to be a driving force behind this therapy, but in many TIL cultures the frequency of these cells is low. Here, we demonstrate a technology to enrich defined antigen‐specific T‐cell populations, and show that this can be utilized to enhance the tumor‐killing capacity of TIL. Abstract : Tumor infiltrating lymphocyte (TIL) therapy has shown objective clinical response rates of 50% in stage IV melanoma patients in a number of clinical trials. Nevertheless, the majority of patients progress either directly upon therapy or after an initial period of tumor control. Recent data have shown that most TIL products that are used for therapy contain only low frequencies of T cells reactive against known melanoma‐associated epitopes. Because of this, the development of a technology to create T‐cell products that are enriched for reactivity against defined melanoma‐associated antigens would seem valuable, both to evaluate the tumoricidal potential of T cells directed against different antigen classes and to potentially increase response rates. Here, we developed and validated a conditional MHC streptamer‐based platform for the creation of TIL products with defined antigen reactivities. We have used this platform to successfully enrich both high‐frequency (≥1%) and low‐frequency (<1%) tumor‐specific CD8 + T‐cell populations, and thereby created T‐cell products with enhanced tumor recognition potential. Collectively, these data demonstrate that selection of antigen‐specific T‐cell populations can be used to create defined T‐cell products for clinical use. This strategy thus forms a highly flexible platform for the development of antigen‐specific cell products for personalized cancer immunotherapy.